1992
DOI: 10.1128/jvi.66.5.3257-3262.1992
|View full text |Cite
|
Sign up to set email alerts
|

Consistent transcription of the Epstein-Barr virus LMP2 gene in nasopharyngeal carcinoma

Abstract: Two species of the Epstein-Barr virus-encoded latent membrane protein 2, LMP2A and LMP2B, are generated by alternative splicing, each species having a distinct first exon. LMP2 transcription in undifferentiated nasopharyngeal carcinoma (NPC), which is consistently associated with the Epstein-Barr virus, was investigated. Fifteen NPC specimens were analyzed by Northern (RNA) blot and RNA-based polymerase chain reaction; the LMP2A transcript was present in all specimens except one. In some specimens the LMP2B tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(51 citation statements)
references
References 19 publications
1
50
0
Order By: Relevance
“…Analysis of undifferentiated NPC, and more recent studies on receptor-positive epithelial cells exposed to the virus in vitro, have identified a number of viral markers characteristic of non-productive infection in an epithelial environment. These are expression of the small non-polyadenylated nuclear RNAs (EBERs), of the spliced rightward-running BamHI A RNAs, and of a BamHI F promoter-driven EBNAl mRNA with a unique BamHI FQ/U/K splice structure (Wu et al, 1991;Brooks et al, 1992;Busson et al, 1992;Gilligan et al, 1991;Li et aL, 1992;Niedobitek et al, 1992). The EBERs are by far the most abundant latency-associated transcripts and are readily detectable by in situ hybridization (Wu ef al., 1991;Niedobitek et al, 1992) whilst the other less abundant RNAs are detectable by polymerase chain reaction-mediated cDNA amplification across splice junctions (Brooks ef al., 1992).…”
Section: Results); (Ii) Cdna Amplification Across Defined Splice Juncmentioning
confidence: 99%
“…Analysis of undifferentiated NPC, and more recent studies on receptor-positive epithelial cells exposed to the virus in vitro, have identified a number of viral markers characteristic of non-productive infection in an epithelial environment. These are expression of the small non-polyadenylated nuclear RNAs (EBERs), of the spliced rightward-running BamHI A RNAs, and of a BamHI F promoter-driven EBNAl mRNA with a unique BamHI FQ/U/K splice structure (Wu et al, 1991;Brooks et al, 1992;Busson et al, 1992;Gilligan et al, 1991;Li et aL, 1992;Niedobitek et al, 1992). The EBERs are by far the most abundant latency-associated transcripts and are readily detectable by in situ hybridization (Wu ef al., 1991;Niedobitek et al, 1992) whilst the other less abundant RNAs are detectable by polymerase chain reaction-mediated cDNA amplification across splice junctions (Brooks ef al., 1992).…”
Section: Results); (Ii) Cdna Amplification Across Defined Splice Juncmentioning
confidence: 99%
“…However, EBV can be routinely detected in circulating latently infected B cells of healthy seropositive individuals, whereas detection of KSHV in blood is rare [44][45][46]. The preferential ability to detect serum IgA responses against EBV vs KSHV on the protein arrays may also be related to in vivo infection of mucosal epithelial cells by EBV because the most frequently observed antigens were latency proteins or lytic replicative proteins known to be expressed in epithelial cells [47][48][49][50]. KSHV infects endothelial cells as well as B cells, but the contribution of endothelial cells to in vivo viral persistence is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…(C) Cells from the peritoneal cavity of wildtype C57/Bl6 and mMT recipient mice were stained for B220 and CD5 to detect B1 B cells. (111,112) and elevated titers of antibodies to LMP2A found in 64% of NPC patients (113). The inability of LMP2A to transform human foreskin kerotinocytes and the absence of tumor formation in transgenic mice suggest that LMP2A itself is not oncogenic (114,115).…”
Section: Ebv Lmp2amentioning
confidence: 99%